Pervaporation, vapour permeation and membrane distillation : principles and applications - Basile, Angelo; Figoli, Alberto; Khayet, Mohamed, 1966- (Kidlington, UK : Woodhead Publishing, an imprint of Elsevier, 2015)
Vapour permeation and membrane distillation are two emerging membrane technologies for the production of vapour as permeate, which, in addition to well-established pervaporation technology, are of increasing interest to academia and industry. As efficient separation and concentration processes, they have high potential for use in the energy, water, chemical, food and pharmaceutical sectors. Part One begins by covering the fundamentals, preparation and characterization of pervaporation, before going on to outline the associated systems and applications. State of the art uses, future trends.
7.4 Conclusion and sources of further information and advice7.5 Future trends in development of membrane vapor separation; References; 7. Appendix: notation and abbreviations; 8 -- Vapour permeation modelling; 8.1 Introduction; 8.2 Fundamentals of vapour permeation modelling into dense polymeric membranes; 8.3 Diffusion modelling; 8.4 Solubility modelling; 8.5 Vapour permeation in mixed matrix membranes and heterogeneous systems; 8.6 Future trends; 8.7 Conclusions; References; 8. Appendix: notation and abbreviations; 9 -- New generation vapour permeation membranes; 9.1 Introduction
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Membranes (Technology); Pervaporation; Membrane separation; Vapors -- Permeability; Membrane distillation; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books; Electronic books